Impact of Management Strategies on the Outcome of Persistent Pulmonary Hypertension of the Newborn - Agha, Hala; Tantawy, Amira El; Iskander, Iman; Samad, Amany Abdel (Cardiology and Cardiovascular Medicine, 2017)
Objectives: To evaluate the associated risk factors and to determine the impact of management strategies on the outcome of PPHN. Study Design: Prospective descriptive study in tertiary center included 40 neonates having PPHN. All patients received the conventional therapy for PPHN, sildenafil as adjuvant therapy was added in cases of failure. Results: The study included 23 males, 17 females with a mean gestational age 37.25 ± 2.6 weeks. Male patients had significantly higher systolic pulmonary artery pressure (SPAP) and higher mortality rate compared to females [7/23 (30.4%) versus 1/17 (5.9%), p = 0.04]. Infants of diabetic mothers had significantly higher mortality rate (p = 0.003). Components of the blood gases; PH, PCO2, HCO3 improved dramatically after completion of the different lines of treatment (p = 0.001). A statistical significant drop of SPAP after application of the different modalities of treatment (p = 0.001). Addition of sildenafil was effective in the reduction of the duration of NICU stay and SPAP below 40 mmHg and (p = 0.001, p =0.0001, respectively). The overall mortality rate was 8/40 neonates (20%), however, the mortality among the patients who received sildenafil in addition to conventional therapy was 1/14 neonates (7.14%) of those group with p = 0.001). Conclusion: In the absence of inhaled nitric oxide, conventional therapy is effective in the management of PPHN. The use of oral sildenafil as an adjuvant therapy is effective in reduction of the systolic pulmonary artery pressure and the hospital stay.